Ação pública no campo da música no Rio Grande do Norte: atores, representações, processos, instituições e resultados - Padilha, Yuri de Lima (2021)
This thesis aims to analyze how state and non-state actors involved with music, in their public action, implement cultural policies for music in Rio Grande do Norte (RN/Brazil). It is based on the public action sociology, a theoretical approach grounded on the new institutionalism. The analysis used the Public Policy Pentagon (PPP) established by Lascoumes and Le Galès (2012a), based on public action, configured in related dimensions - actors, processes, representations, institutions, and results. The qualitative research carried out 24 interviews with actors, from the metropolitan and inland regions of RN, chosen for their role in the music field. Based on the interviews, the analysis of the public action dynamics reveals that although there are no normative guidelines guiding and conducting state action in the music scope, there are actions being designed and implemented with a relative civil society actors influence, with repercussions for music. This fact shows that it is assertive to think about public policies both for what they present and for what they fail to do. There is an institutional vacuum in the policies conduct for the music field in terms of specific instruments, but it is possible to say that the few instruments that do exist are somehow appropriated by music, like notices and tax incentive law. Furthermore, it is also possible to point out that in the institutional vacuum emerges policy proposals for culture and, by extension, for music. Thus, the thesis defends that the different actors linked to the music artistic expression establish different forms of interactions, creating and / or occupying formal and / or informal decisionmaking spaces, based on the representations they share about the musical world specificities, to influence the policies implementation, and produce results that support the consolidation of existing musical expressions and foster new musical languages. As a result of this statement, it can also be said that public action in which state and non-state actors are involved also implies policies formulation such as the normative frameworks proposal for culture. And, in this way, they influence the setting of a public agenda for culture and, particularly, for music that contemplates the most diverse aspects, from the structuring of the field to the role that the State must assume as a protagonist in the promotion and preservation of culture.